Agricultural waste management (AWM) system in Mukim Ulu Telom, Cameron Highlands, Pahang / Nurul Syamimi Fauzi and Nor Eeda Ali - Fauzi, Nurul Syamimi; Ali, Nor Eeda (2019)
- Cameron Highlands is one of the largest area of agriculture sector in peninsular Malaysia because of the temperature are mild are very conducive to a wide range of sub-tropical crops. Nowadays, the volume of agriculture waste generation in Cameron Highlands are increased due to the increasing number of production of agriculture plantation. It happen because of agriculture waste management (AWM) system still very lack comprehensive especially on the understanding and involvement in the waste management system and the awareness on important of agriculture waste management in Cameron Highlands are in low level. Based on these issues came out with the aim which is to integrate the proper AWM system. The objective is to investigate the various stages that are involved in agriculture waste management system and examine the role of formal and informal stakeholders in agriculture waste management system and the policies and strategies involved in AWM system. A qualitative method was used for this research by observing the process (stages) of agriculture waste management system in study area. The outcome of this research is expected to assist the stakeholder involved, to enhance the proper AWM system and to increase the target of waste minimisation in Malaysia.